Self-esteem and its relationship with sexual risk behavior for HIV in migrants: systematic review - Tizoc-Márquez, Arodi (Universidad de Sonora, 2021)
Introduction: The vulnerable situation faced by the migrant, brings emotional changes that can facilitate or hinder their adaptation to risk behaviors, self-esteem can be relevant in the sexual behaviors that the migrant has. Objective: To analyze the scientific evidence on the relationship of self-esteem and sexual risk behavior for HIV in migrants. Method: A systematic review was made based on the recommendations of the PRISMA protocol, the literature search was carried out in the electronic databases, Pubmed, Ebscohost, Scopus, Web of Science and SciELO Citation Index, for the search strategy the DeCS and MeSH, the quality of the literature was validated. Results: The relationship of self-esteem with sexual behaviors is not congruent, the higher self-esteem predicts risky sexual relations (lower probability of using condoms) (β = -40, p <.01), there is an association of lower self-esteem with a higher probability of sex and protection with a casual partner (OR = 1.82). Conclusions: There is inconsistency in the evidence about self-esteem is a protective or risk factor for the migrant's sexual behavior. However, the studies analyzed do not highlight sexual risk behaviors for HIV, and the migrant is population that is constantly changing and multiple factors influence its decision-making and changes, therefore is important continue to be addressed mainly this population.